Estereotomía topológica : como instrumento innovativo en la configuración morfológica del paisaje urbano-arquitectónico - Períes, Lucas (2015)
The following research integrates the concepts of topological geometry in the architectural design process. This refers to an emerging phenomenon from professional avant-garde production still lacking of systematized methodological tools. These are the basis for the development of a strategic instrument of formal production denominated topological stereotomy. Stereotomy is a way of morphological configuration that has been atavistically used by men. Topology is one of the newest branches of mathematics that deals with continuity and equivalence of shapes and systems, regardless of dimensions. The conjunction of both terms leads to a subcategory of traditional stereotomy that allows for a particular way of formal configuration. The topological principles applied to the design process cause the generation of continuous, intertwined and fluid spacialities where the ground archetype plays a major role in the production of topomorphic landscapes. The research provides a theoretical and procedural contribution on the topic: classification and relation of the existing knowledge, characterization of intervening design logic and the generation of specific conceptual and operational tools to be applied in design, teaching and or critic of the urban architectonic landscape.